Deleuze and Guattari's A thousand plateaus : a critical introduction and guide - Adkins, Brent, 1969- (Critical Introductions and Guides., 2015)
The sheer volume and complexity of Deleuze and Guattari's A Thousand Plateaus can be daunting. What is an assemblage? What is a rhizome? What is a war machine? What is a body without organs? What is becoming-animal? Brent Adkins demonstrates that all the questions raised by A Thousand Plateaus are in service to Deleuze and Guattari's radical reconstruction of the methods and aims of philosophy itself. To achieve this he argues that the crucial term for understanding A Thousand Plateaus is 'assemblage.' An assemblage is Deleuze and Guattari's answer to the perennial philosophical question, 'What is a thing?' and they assert that assemblages are always found on a continuum between stasis and change. Using clear language and numerous examples, each chapter analyses an individual plateau and examines the tendencies toward both stasis and change for each assemblage found there - be it social, political, psychological, musical, biological or linguistic. Key Features. Explains all the major terms found in A Thousand Plateaus in clear language Each chapter corresponds to a 'plateau' for ease of reference Provides a singular interpretation of the work in terms of assemblages and connecting that interpretation with traditional and contemporary debates within philosophy